2013
DOI: 10.1136/eb-2012-101136
|View full text |Cite
|
Sign up to set email alerts
|

The possible effects of depressive symptoms on risk of preterm birth are clouded by lack of control over confounding factors

Abstract: The possible effects of depressive symptoms on risk of preterm birth are clouded by lack of control over confounding factors Kimberly A Yonkers Commentary on: Straub H, Adams M, Kim JJ, et al. Antenatal depressive symptoms increase the likelihood of preterm birth. Am J Obstet Gynecol 2012;207:e1-4. ContextDepressive symptoms have been associated with risk of preterm birth (PTB). 1 Straub and colleagues sought to explore whether an elevated score on the Edinburgh Postnatal Depression Scale (EPDS) is associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(6 reference statements)
0
1
1
Order By: Relevance
“…[57] However, other investigators have found no increased odds of PTB in relation to antepartum depression. Potential reasons posited for null findings in prior studies have been confounding by illicit substances and other psychosocial conditions such as exposure to trauma and violence [58] although these reasons are unlikely to explain our observed findings. Self-reported Illicit drug use in our study population is only 0.5%.…”
Section: Discussioncontrasting
confidence: 58%
“…[57] However, other investigators have found no increased odds of PTB in relation to antepartum depression. Potential reasons posited for null findings in prior studies have been confounding by illicit substances and other psychosocial conditions such as exposure to trauma and violence [58] although these reasons are unlikely to explain our observed findings. Self-reported Illicit drug use in our study population is only 0.5%.…”
Section: Discussioncontrasting
confidence: 58%
“…A second set of findings is that many of the obstetric factors that have long been associated with child health and development – birth weight, gestational age – are predicted from maternal mood and stress in pregnancy (Grote et al., , but see Littleton, Breitkopf, & Berenson, ; Yonkers, ). The lesson here is that presumed established risk factors for poor future child neurobehavioral development may themselves be proxies for prenatal events and exposures.…”
Section: Evidence Base and Mechanisms Of Effectmentioning
confidence: 99%